HUBUNGAN SPIRITUALITAS DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL TERMINAL (GGT) YANG MENJALANI HEMODIALISIS DI RSUD KABUPATEN BULELENG - Rika Septiani; Gusti Ayu Ary Antari; Made Oka Ari Kamayani (Coping: Community of Publishing in Nursing, 2021)
Patients with kidney failure must receive replacement therapy for kidney function; one of them ishemodialysis. Long-term hemodialysis therapy causes changes in aspects of life; one of them ispsychological changes that give rise to response to spiritual expressions in the form of negative orpositive responses. Negative response will have an impact on the quality of life patients. This study aimedto determine whether there was a relationship between spirituality and the life quality of kidney failurepatients that underwent hemodialysis in RSUD Buleleng. This research is a descriptive correlational studywith a cross-sectional design and purposive sampling technique. The amount of sample in this study was92 patients who underwent hemodialysis in RSUD Buleleng. The Spearman Rank test results onspirituality and quality of life variables obtained p-value 0.001 (p <0.05), which means there was amoderate positive relationship between spirituality and quality of life kidney failure patients thatunderwent hemodialysis in RSUD Buleleng. So it can be concluded that if spirituality is high, the qualityof life will be okay. Suggested for hemodialysis nurses can implement holistic treatments expecially toimprove aspects of spirituality so that they can maintain the life quality of patients that undergoeshemodialysis.